2011
DOI: 10.3354/ame01506
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variation in denitrification and in the denitrifier community in a boreal lake

Abstract: We investigated the spatial and temporal variation in denitrification rates (isotopepairing technique, IPT) and in the denitrifier community (examination of gene nirK by denaturinggradient gel electrophoresis [DGGE] of microbial DNA) in the sediments of a boreal, clear-water, eutrophic lake using samples collected from shallow littoral, deep littoral and shallow profundal sediments during early summer, mid-summer, autumn and winter. The measured denitrification rates (44 to 613 µmol N m) are among the lowest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 86 publications
2
31
1
Order By: Relevance
“…Our study also showed the linkage between NO 3 − concentration and N 2 O accumulation, which is in agreement with previous work in boreal lakes [18]. Based on previously published N 2 production rates for five of the lakes in this study [29, 32] (unpublished results), the N 2 O production rates reported here correspond to 0.2−1.7% of the total gaseous N production (N 2 O/(N 2 +N 2 O) ratio). These values fall within the range of previously reported estimates (0.1–4.1%) for freshwater systems [33].…”
Section: Discussionsupporting
confidence: 93%
“…Our study also showed the linkage between NO 3 − concentration and N 2 O accumulation, which is in agreement with previous work in boreal lakes [18]. Based on previously published N 2 production rates for five of the lakes in this study [29, 32] (unpublished results), the N 2 O production rates reported here correspond to 0.2−1.7% of the total gaseous N production (N 2 O/(N 2 +N 2 O) ratio). These values fall within the range of previously reported estimates (0.1–4.1%) for freshwater systems [33].…”
Section: Discussionsupporting
confidence: 93%
“…For DNA‐analysis and sediment characteristics, three replicate samples of the uppermost sediment (0–2 cm) were collected from each sampling point using Sandman sediment sampler, and stored at −20°C. Nitrate + nitrite (NO x − ) and ammonium (NH 4 + ) from water above the sediment surface (collected with Limnos sampler) were determined as in Rissanen and colleagues (). Wastewater discharge samples (100 ml of effluent water) were collected from all WWTPs.…”
Section: Methodsmentioning
confidence: 99%
“…Obviously, the spatial variation in the BCC in the sediment of small deep lakes (Rissanen et al 2011) or large deep lakes (e.g. Baikal, Constance, Kinneret; Pester et al 2004, Shubenkova et al 2005, Schwarz et al 2007, Deutzmann et al 2011) depends on the depth of the lake and, in the case of large lakes, the shape of the lake basin, leading to diverse conditions in the basins of these lakes.…”
Section: Discussionmentioning
confidence: 99%